2021
DOI: 10.1155/2021/9920280
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Preclinical Training on Root Canal Treatment Technical Quality and Confidence Level of Undergraduate Dental Students

Abstract: Objectives. The aim of this study was to investigate the influence of exposure to additional preclinical endodontic training on undergraduate students’ technical quality of root canal treatment and overall confidence levels in endodontics. Methods. Technical quality of root canal treatment performed clinically by fifth-year undergraduate students was evaluated and divided into two groups: Group 1, teeth treated by students who had attended both a preclinical endodontic block course and an elective preclinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…However, students were not confident in their preclinical practice of pulp therapies. A large proportion of students wanted more preclinical sessions for pulp therapy practice but Barakat et al ( 2021 ) found that additional preclinical training in root canal treatment (in the permanent dentition) did not significantly improve confidence. Students currently receive only one three-hour preclinical session to practice a pulpotomy on a deciduous tooth.…”
Section: Discussionmentioning
confidence: 99%
“…However, students were not confident in their preclinical practice of pulp therapies. A large proportion of students wanted more preclinical sessions for pulp therapy practice but Barakat et al ( 2021 ) found that additional preclinical training in root canal treatment (in the permanent dentition) did not significantly improve confidence. Students currently receive only one three-hour preclinical session to practice a pulpotomy on a deciduous tooth.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the Saudi students are trained to treat cases of minimal to moderate level of complexity. Several studies found that undergraduate students were least confident in treating the molars among other teeth groups [ 31 – 33 , 35 , 42 , 43 ]. Interestingly, the quality of RCT done in the Saudi public health sector was better than in the Saudi private sector and even better than some of the internationally reported findings [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in another study, a high proportion of final-year dental students were not confident in performing root canal treatment on multirooted posterior teeth [18]. Thus, in dental education, there is a need for hands-on pre-clinical training before a patient's treatment is carried out for the first time [16,[19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%